PROGNOSTIC VALUE OF ENDOTHELIAL DYSFUNCTION IN CORONARY AND BRACHIAL ARTERIES, AND COMMON RISK FACTORS IN DEVELOPMENT OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH MICROVASCULAR ANGINA - G. N. Soboleva; V. K. Fedulov; A. N. Samko; I. V. Levitsky; A. N. Rogoza; T. V. Balakhonova; Yu. A. Karpov (Российский кардиологический журнал, 2017)
Aim. To study  prognostical  significance  of vasomotor  disorder  of coronary  and brachial  arteries,   and  traditional  risk factors  in development   of  cardiovascular complications in patients with microvascular angina (MVA) and cardial syndrome X; a retrospective 12-year observation.Material and methods. Totally, 41 patient included, with MVA (40 females/1 male), mean  age  at the moment  of inclusion 43±4,1  y.o., 15% smokers).  Endotheliumdependent vasodilation (EDV) of coronary arteries  was assessed via intracoronary acetylcholine load, EDV of brachial artery — via high-resolution ultrasound in active hyperemia test.Results. It was found that in brachial EDV <4,7% group the risk of cardiovascular complications  (p<0,05)  is higher for 9-18  years  of observation.  Baseline  EDV of coronary arteries in the study did not influence survival rate in MVA patients.Conclusion. Significant influence on cardiovascular  events occurring in long-term follow-up of MVA  patients,  had  the  risk factors  as  smoking  and  brachial  artery endothelial dysfunction.